Inter-individual variability of early life stages of a model marine invertebrate with a bi-phasic life cycle is shaped by contrasting oceanographic conditions - Leal, Miguel Costa; Rey, Felisa; Ferreira, Guilherme Duarte; Domingues, M. Rosário; Calado, Ricardo (Frontiers in Marine Science, 2022)
Inter-individual variability plays a key role in species resilience. This, however, is difficult to assess in marine invertebrates with complex life cycles due to the inherent difficulty of sampling individuals in oceanic environments throughout their ontogeny. This study monitored the effect of contrasting oceanographic conditions, namely downwelling and upwelling, on the inter-variability of embryos and megalopae (the final larval stage) of the model brachyuran crab Carcinus maenas. We assessed i) the heterogeneity of energetic reserves, biomass, elemental composition, and isotopic niche in these early life stages, and ii) the effect of oceanographic conditions (up- and downwelling) on inter-individual variability. Indeed, organisms developing during downwelling consistently exhibited a higher heterogeneity than those developing during upwelling. While this finding suggests a higher resilience during downwelling, the overall condition of individuals was better during upwelling (i.e., higher C:N), irrespective of the developmental stage. Altogether, our data suggests that trophic history experienced under contrasting oceanographic conditions shape the plasticity of C. maenas populations and cascades over different life stages.